Improved cultural detection of Burkholderia cepacia from sputum in patients with cystic fibrosis. Issue 10 (1st October 2001) - Wright, R M; Moore, J E; Shaw, A; Dunbar, K; Dodd, M; Webb, K; Redmond, A O B; Crowe, M; Murphy, P G; Peacock, S; Elborn, J S
Abstract : Aims —To evaluate the sensitivity and specificity of two selective media for the isolation of Burkholderia cepacia from sputum specimens in patients with cystic fibrosis (CF). Methods —In total, 149 expectorated sputum specimens from 113 patients with CF (32 cepacia colonised patients and 81 non-cepacia colonised patients) attending three CF centres were examined for the presence of B cepacia on two selective media: (1) MAST selective agar, a commercially available selective medium widely used in the UK and (2) bcsa (B cepacia selective agar), a new medium recently described, which is used predominantly in North America. Results—Burkholderia cepacia was isolated from 53 of 149 (35.6%) specimens examined, representing 32 of 113 (28.3%) patients, using both the MAST and BCSA media. Growth was most rapid on BCSA with all (53 of 53) isolates detectable after 48 hours, compared with 50 of the 53 isolates on MAST agar, with the remaining three isolates detectable at five days. Twenty eight contaminants were identified on MAST agar and 13 on BCSA agar; mainly Alcaligenes xylosoxidans and yeast on MAST agar and Flavobacterium indologenes on BCSA medium. BCSA was equivalent to MAST agar in its ability to isolate B cepacia from patients with CF with a history of B cepacia infection. Conclusions—The increased selectivity and reduced time to detection of BCSA makes it an attractive alternative to MAST. However, its present limited commercial availability in the UK may delay its use in routine diagnostic laboratories because of complications with media preparation and quality control.